Repeat radiosurgery for cerebral arteriovenous malformations - Awad, Ahmed J. (J Clin Neurosci, 2015)
We perform a systematic review of repeated radiosurgery for cerebral arteriovenous malformations (AVM) with an emphasis on lesion obliteration rates and complications. Radiosurgery is an accepted treatment modality for AVM located in eloquent cortex or deep brain structures. For residual or persistent lesions, repeated radiosurgery can be considered if sufficient time has passed to allow for a full appreciation of treatment effects, usually at least 3 years. A systematic review was performed in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. References for this review were identified by searches of MEDLINE, Web of Science and Google Scholar databases. A total of 14 studies comprising 733 patients met the review criteria and were included. For series that reported target dose at both first and repeat treatments, the weighted means were 19.42 Gy and 19.06 Gy, respectively. The mean and median obliteration rate for the repeat radiosurgery treatments were 61% (95% confidence interval 51.9–71.7%) and 61.5%, respectively. The median follow up following radiosurgery ranged from 19.5 to 80 months. Time to complete obliteration after the repeat treatment ranged from 21 to 40.8 months. The most common complications of repeated radiosurgery for AVM included hemorrhage (7.6%) and radiation-induced changes (7.4%). Repeat radiosurgery can be used to treat incompletely obliterated AVM with an obliteration rate of 61%. Complications are related to treatment effect latency (hemorrhage risk) as well as radiation-induced changes. Repeat radiosurgery can be performed at three years following the initial treatment, allowing for full realization of effects from the initial treatment prior to commencing therapy.